(2p-1)(p+1)=0

Simple and best practice solution for (2p-1)(p+1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2p-1)(p+1)=0 equation:


Simplifying
(2p + -1)(p + 1) = 0

Reorder the terms:
(-1 + 2p)(p + 1) = 0

Reorder the terms:
(-1 + 2p)(1 + p) = 0

Multiply (-1 + 2p) * (1 + p)
(-1(1 + p) + 2p * (1 + p)) = 0
((1 * -1 + p * -1) + 2p * (1 + p)) = 0
((-1 + -1p) + 2p * (1 + p)) = 0
(-1 + -1p + (1 * 2p + p * 2p)) = 0
(-1 + -1p + (2p + 2p2)) = 0

Combine like terms: -1p + 2p = 1p
(-1 + 1p + 2p2) = 0

Solving
-1 + 1p + 2p2 = 0

Solving for variable 'p'.

Factor a trinomial.
(-1 + -1p)(1 + -2p) = 0

Subproblem 1

Set the factor '(-1 + -1p)' equal to zero and attempt to solve: Simplifying -1 + -1p = 0 Solving -1 + -1p = 0 Move all terms containing p to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1p = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1p = 0 + 1 -1p = 0 + 1 Combine like terms: 0 + 1 = 1 -1p = 1 Divide each side by '-1'. p = -1 Simplifying p = -1

Subproblem 2

Set the factor '(1 + -2p)' equal to zero and attempt to solve: Simplifying 1 + -2p = 0 Solving 1 + -2p = 0 Move all terms containing p to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2p = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2p = 0 + -1 -2p = 0 + -1 Combine like terms: 0 + -1 = -1 -2p = -1 Divide each side by '-2'. p = 0.5 Simplifying p = 0.5

Solution

p = {-1, 0.5}

See similar equations:

| -4x-15=-31 | | 5-23=9x-5-8x | | -3(y-3y)+9=-2(4y-y)+1+11y | | 8+5x-1-3x=2x+3+3x+1-4x | | 3(x+8)-3x=-2(-4x+2) | | y(2/y) | | 15-6x=5-8x | | -3(x+6)+5=7(x+4)+1 | | 41/28=7/x | | 3a+9-a+8= | | 7(x-4)+8=3(x-4) | | 112-x=161 | | 12-2c=c | | 2x^2-4kx+3=0 | | 7x+7(-3x-11)=-161 | | -8-10=-1+7y | | -v+269=170 | | 0.9x-0.3(5-x)=3.9 | | 36x^3-4x=0 | | .50y+2.3=1.65 | | 10+9x=-22+x | | 83=-2x+5(-3x-14) | | 90=253-w | | x^4-7*2+12=0 | | -7+x+7x=41 | | 10+9x=-20+x | | x/6=-43 | | 41x=1974 | | -7-7(-4x-9)=168 | | 6z^2-7z+12=0 | | x+.06x=27120 | | 10sinx-1=0 |

Equations solver categories